PENGARUH MOTIVASI BERWIRAUSAHA TERHADAP KEBERHASILAN USAHA BUDIDAYA MAGGOT DI DESA OLAYAMA KECAMATAN HURUNA KABUPATEN NIAS SELATAN - Halawa, Putra Sumarlin (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
The aim of this research is to find out whether entrepreneurial motivation influences the success of the maggot cultivation business in Olayama Village, Huruna District, South Nias Regency. With a total of 31 respondents, the population and sample for this quantitative research are maggot business entrepreneurs. Data collection techniques include research instruments such as surveys and documentation. The methodology used is a fundamental approach to data analysis using linear regression. The tcount value is 4.358 > ttable 2.045 according to research findings. Research shows that in Olayama Village, Huruna District, South Nias Regency, entrepreneurial motivation has a significant and positive effect on the profitability of maggot cultivation businesses. Some of the recommendations suggested in this research are as follows: (1) It is hoped that maggot farm owners in Olayama Village will be increasingly encouraged to develop their businesses. Owners of maggot cultivation businesses in Olayama Village, Huruna District, are encouraged to continue learning and honing their company development skills so that they do not experience failure in this regard.